A multidisciplinary approach to mental illness: do inflammation, telomere length and microbiota form a loop? A protocol for a cross-sectional study on the complex relationship between inflammation, telomere length, gut microbiota and psychiatric disorders. Issue 1 (26th January 2020) - Manchia, Mirko; Paribello, Pasquale; Arzedi, Carlo; Bocchetta, Alberto; Caria, Paola; Cocco, Cristina; Congiu, Donatella; Cossu, Eleonora; Dettori, Tinuccia; Frau, Daniela V; Garzilli, Mario; Manca, Elias; et al.
Abstract : Introduction: Severe psychiatric disorders are typically associated with a significant reduction in life expectancy compared with the general population. Among the different hypotheses formulated to explain this observation, accelerated ageing has been increasingly recognised as the main culprit. At the same time, telomere shortening is becoming widely accepted as a proxy molecular marker of ageing. The present study aims to fill a gap in the literature by better defining the complex interaction/s between inflammation, age-related comorbidities, telomere shortening and gut microbiota in psychiatric disorders. Methods and analysis: A cross-sectional study is proposed, recruiting 40 patients for each of three different diagnostic categories (bipolar disorder, schizophrenia and major depressive disorder) treated at the Section of Psychiatry and at the Unit of Clinical Pharmacology of the University Hospital Agency of Cagliari (Italy), compared with 40 age-matched and sex-matched non-psychiatric controls. Each group includes individuals suffering, or not, from age-related comorbidities, to account for the impact of these medical conditions on the biological make-up of recruited patients. The inflammatory state, microbiota composition and telomere length (TL) are assessed. Ethics and dissemination: The study protocol was approved by the Ethics Committee of the University Hospital Agency of Cagliari (PG/2018/11693, 5 September 2018). The study is conducted in accordance with the principles of good clinical practice and the Declaration of Helsinki, and in compliance with the relevant Italian national legislation. Written, informed consent is obtained from all participants. Participation in the study is on a voluntary basis only. Patients will be part of the dissemination phase of the study results, during which a local conference will be organised and families of patients will also be involved. Moreover, findings will be published in one or more research papers and presented at national and international conferences, in posters or oral communications.